KONSEP MANUSIA UTAMA MENURUT AL-KINDI - Ramdani, Dani (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2023)
This article aims to explain the superiority human concept according to al-Kindi. The main human initiated by al-Kindi is a concept commensurate with the meaning of the idea of the perfect human (al-insan al-kamil). The perfect man himself is a key concept in the Islamic philosophical tradition, especially in the scientific discipline of mysticism. In the perfect man are shown all the qualities of moral wisdom, which in turn, describe the names and attributes of Allah to a complete degree. The perfect man bridged mankind with God. In another terminology, al-Kindi calls this perfect human being the superiority human term (al-insan al-fadil).